Farinha de vísceras de aves na alimentação de alevinos de lambari - Signor, Arcangelo Augusto; Boscolo, Wilson Rogério; Bittencourt, Fabio; Feiden, Aldi; Reidel, Adilson [UNESP] (Universidade Federal de Santa Maria (UFSM), 2008)
O lambari, Astyanax altiparanae, é uma espécie muito comum em rios nacionais, com grande potencial para a piscicultura nacional. Ele apresenta crescimento rápido e carne de excelente sabor, sendo muito apreciado com petisco e como isca viva para a pesca esportiva. A farinha de vísceras de aves é uma importante fonte protéica de origem animal. O trabalho foi realizado com o objetivo de avaliar a inclusão de farinha de vísceras de aves (FV) em rações para alevinos de lambari. Foram utilizados 125 alevinos, apresentando peso e comprimento inicial médio de 0,080±0,002g e 1,86±0,20cm, respectivamente, distribuídos em 25 aquários. As rações foram formuladas de forma a conter 0, 5, 10, 15 e 20% de FV na dieta. O arraçoamento foi realizado quatro vezes ao dia, na forma farelada e à vontade. O valores médios de peso final (1,47, 1,92, 2,02, 2,11 e 2,15g) e comprimento final (4,40, 4,78, 4,92, 4,92 e 5,08cm) dos alevinos de lambari apresentaram aumento linear (P<0,05) diretamente proporcional aos níveis de inclusão (0, 5, 10, 15 e 20% de FV) nas rações. A sobrevivência (88, 96, 92, 76 e 88%) e a conversão alimentar aparente (4,58, 3,29, 3,25, 3,92 e 3,34) não apresentaram diferença (P<0,05) entre os níveis de FV na dieta. A inclusão de farinha de vísceras de aves em rações à base de ingredientes de origem vegetal melhora o desempenho e o teor protéico da carcaça.

The lambari Astyanax altiparanae, is a very common species in the national rivers, with great potential for the national psyculture. It presents a fast growth and meat of eccellent flavor, being very appreciate like a delicacy and like an alive bait to sportive fishing. The poultry by-product meal is an important proteinic source from animal origin. The research was carried out with the objective to evaluate the poultry by-product meal inclusion (FV) in rations for lambari fingerlings. 125 fingerlings presenting average weight and initial length of 0.080±0.002g and 1.86±0.20cm respectively were used, they were distributed in 25 aquariums. The rations were formulated in form to contain 0, 5, 10 15 and 20% of FV in the diet. The ration giving was carried through four times a day, in a braning form and at the will. The avarage values of final weight (1.47, 19.2, 2.02, 2.11 and 2.15) and final length of (4.40, 4.78, 4.92 and 5.08cm) of the lambari fingerlings had presented linear increase (P<0.05) directly proportional to the inclusion levels of (0, 5, 10, 15 and 20% of FV) in the rations. The survival (88, 96, 92, 76 and 88%) and apparent alimentary conversion (4.58, 3.29, 3.25, 3.92 and 3.34) had not presented difference (P<0.05) among the (FV) levels in the diet. The inclusion of poultry by-product meal in rations based in ingredients of vegetable origin provides the performance and the proteic text of the carcass.
Poultry by-product meal in lambari fingerlings diet
Keywords: resíduos industriais; nutrição de peixes; peixes nativos; industrial residues; fish nutrition; native fish